Analisis Pengaruh Remunerasi terhadap Kinerja Pegawai pada Tenaga Kependidikan Tetap Non PNS di Lingkungan Kantor Pusat Universitas Brawijaya - Fatayati, Siti Unun; Gani, Abdul Juli Andi; Hanafi, Imam (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
This study aims to examine the significance of the effect of remuneration on employee performance with workload and discipline as an intervening variable for non permanent civil servants in UB's head office. The method used in this research is descriptive quantitative research method. The sample in this research is non civil servant education staff in UB head office with a total of 200 respondents. Data analysis used is path analysis. The results showed the variable remuneration (X1) has a positive and significant effect on the workload variable (X2). The remuneration variable (X1) has a positive and significant effect on the discipline variable (X3). The remuneration variable (X1) has a positive and significant effect on the performance variable (Y1). The workload variable (X2) has a positive and significant effect on the performance variable (Y1). Discipline variable (X3) have positive and significant effect to performance variable (Y1).